Hemopexin promotes angiogenesis via up-regulating HO-1 in rats after cerebral ischemia-reperfusion injury - Beibei Dong; Zhishen Zhang; Keliang Xie; Yongyan Yang; Yuan Shi; Chenxu Wang; Yonghao Yu (BMC Anesthesiology, 2018)
Abstract Background Ischemia-reperfusion (I/R) is a critical pathophysiological change of ischemic stroke. Heme-oxygenase-1 (HO-1) is a rate-limiting enzyme of eliminating excessive free heme by combining with hemopexin (HPX), a plasma protein contributing to alleviating infarct size due to ischemia stroke. This study was to investigate whether HPX could improve angiogenesis after cerebral ischemia-reperfusion via up-regulating HO-1. Methods Rats were randomly divided into five groups: sham, MCAO, MCAO + Vehicle, MCAO + HPX and MCAO + HPX + protoporphyrin IX (ZnPPIX, an HO-1 inhibitor). Cerebral I/R was induced by MCAO. Saline, vehicle, HPX and HPX + ZnPPIX were respectively given to MCAO group, MCAO + Vehicle group, MCAO + HPX group and MCAO + HPX + ZnPPIX group at the moment after reperfusion by intracerebroventricular injection. Neurological behavioral scores(NBS) was assessed at 24 h and 7d after I/R. Real-time polymerase chain reaction (RT-PCR) was used to analyze the mRNA level of HO-1. Angiogenesis in penumbra area was assessed by immunofluorescence detection at 7d after I/R. Serum endothelial nitric oxide synthase (eNOS) was assessed by enzyme linked immunosorbent assay (ELISA) at 24 h and 7d after I/R. Results Compared with sham group, the NBS and the mRNA levels of HO-1 at 24 h and 7d after I/R in MCAO group decreased notably (P < 0.05), the new vessel density in ischemia penumbra increased notably at 7d after I/R (P < 0.05), the serum eNOS level increased at 24 h and 7d after I/R (P < 0.05). MCAO group and MCAO + Vehicle group showed no significant differences (P > 0.05). In the MCAO + HPX group, compared with MCAO + Vehicle group, the NBS and the mRNA levels of HO-1 increased drastically at 24 h and 7d after I/R (P < 0.05), the new vessel density in ischemia penumbra increased significantly at 7d after I/R (P < 0.05), the serum eNOS level at 24 h and 7d after I/R ascended notably (P < 0.05). Compared with MCAO + HPX group, the NBS assessment, new vessel density and serum eNOS level decreased at corresponding time points after I/R in MCAO + HPX+ ZnPPIX group (P < 0.05). Conclusion HPX can promote angiogenesis after cerebral ischemia-reperfusion injury in rats via up-regulating HO-1.